« Effets-tableaux » et parergon dans Macbeth Meeting the Three Witches par Francesco Zuccarelli et par Henry Füssli d’après Macbeth - Nathalie Padilla (Revue LISA)
During the 18th century, Shakespeare’s Macbeth was a source of inspiration for many painters who tried to underscore the pictorial quality of the play, especially that of Act 1, scene 3. The paper compares the interpretations offered by Henry Fuseli and Francesco Zuccarelli who were both foreign artists belonging to the Royal Academy of London. Their paintings after Act 1, scene 3, of Macbeth offer a visual representation articulated around contrast and convergence: if Fuseli remains faithful to the pivotal emotional intent, seen as the “ergon” here, Zuccarelli almost ignores it, finding a greater interest in the landscape of the scene that fills most of his pictorial space. However, the two works fuse together within the etymology of the term “ergon”, that equates with “work” or “action”. They illustrate the idea of active witchcraft through natural phenomena controlled by the three witches.